Study of Neuromarketing in Consumer Behavior due to Product Logos Color Changes Effect - Denta Rahmadani; Hilman Fauzi; Reza Armanda Lubis; Maya Ariyanti (CEPAT Journal of Computer Engineering: Progress, Application and Technology, 2022)
Consumer behavior can be detected by conducting surveys, but this method lacks the depth of analysis to measure consumer behavior. By utilizing technological and scientific advances through the study of neuroscience, especially in neuromarketing, it is hoped to improve the ability to analyze consumer behavior. Neuromarketing has been widely used to measure consumer behavior through several stimuli, including logo colors. Neuromarketing to the human brain's response is done using electroencephalography (EEG) signal analysis. Data collection was carried out on six students aged 19-24 years. Subjects were given a stimulus of five original logo colors and five logo colors recolored with the number of questions in three sessions. Pre-processing uses a butterwort horde four bandpass filter with a theta-band frequency band in the frequency range of 4-8 Hz. Data on color changes using questionnaires and EEG signal data is processed on spatial and spectral domains to view active areas of short-term memory. The result obtained is the effect of the change in logo color on consumer memory and the active location of short-term memory on the logo's color. Using spatial selection, the number of channels was reduced from 16 to 4 channels or by 75%. The selected channels are in the memory and visual areas.